Contribution to the taxonomy of the Palaearctic species of the genus Laelius Ashmead, mainly from Finland and Sweden (Hymenoptera: Chrysidoidea: Bethylidae) - Vikberg, Veli; Koponen, Martti (Entomologica Fennica, 2005)
A neotype is designated for Bethylus femoralis Förster, 1860 (now Laelius femoralis), and a lectotype for Bethylus rufipes Förster, 1860, nec Say 1824 (now Laelius foersteri Kieffer, 1914). Three new natural species are described from Southern Finland: Laelius borealis Vikberg sp. n. (also in S. Sweden), L. virilis Vikberg sp. n., and L. parcepilosus Vikberg sp. n.. The most common species in Sweden is described as Laelius fumimarginalis Vikberg sp. n. One imported indoor species, L. pedatus (Say), attacks larvae of Reesa vespulae (Milliron) (Coleoptera: Dermestidae) in Finland. The female of Laelius seticornis (Duchaussoy, 1916) is redescribed from La Palma, the Canary islands. All nominal species of Laelius from the Palaearctic region are listed and keys are presented for females and males of those examined.